Improving Decisionmaking in a Turbulent World Strategic Rethink - Ries, Charles P. (RAND Corporation, 2016)
Every president needs a decisionmaking system that harnesses the full capabilities and accumulated wisdom of the U.S. government and the nation's many stakeholders. This Perspective analyzes a range of management challenges in the national security system and presents recommendations for strengthening U.S. decisionmaking and oversight of policy implementation.